2012
DOI: 10.1242/jcs.087049
|View full text |Cite
|
Sign up to set email alerts
|

Samp1 is a component of TAN lines and is required for nuclear movement

Abstract: SummaryThe position of the nucleus is regulated in different developmental stages and cellular events. During polarization, the nucleus moves away from the future leading edge and this movement is required for proper cell migration. Nuclear movement requires the LINC complex components nesprin-2G and SUN2, which form transmembrane actin-associated nuclear (TAN) lines at the nuclear envelope. Here we show that the nuclear envelope protein Samp1 (NET5) is involved in nuclear movement during fibroblast polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 23 publications
(49 reference statements)
4
99
0
Order By: Relevance
“…Sun-2 and Nesprin-2 giant are essential components of these TAN lines, which associate with dorsal actin cables at the cytoplasmic surface of the nucleus and are anchored via lamins to the nuclear interior. The INM proteins Samp and emerin (Borrego-Pinto et al 2012;Chang et al 2013) were also found in these complexes. TAN lines at the nuclear membrane resemble in many aspects FA complexes at the plasma membrane.…”
Section: The Route and Components Of Mechanosensingmentioning
confidence: 95%
“…Sun-2 and Nesprin-2 giant are essential components of these TAN lines, which associate with dorsal actin cables at the cytoplasmic surface of the nucleus and are anchored via lamins to the nuclear interior. The INM proteins Samp and emerin (Borrego-Pinto et al 2012;Chang et al 2013) were also found in these complexes. TAN lines at the nuclear membrane resemble in many aspects FA complexes at the plasma membrane.…”
Section: The Route and Components Of Mechanosensingmentioning
confidence: 95%
“…S2). As nesprin-2G has been shown to colocalize with actin fibers in the perinuclear region and to regulate nuclear motion (Borrego-Pinto et al, 2012;Luxton et al, 2010), the depletion of this LINC protein significantly reduced the fraction of cells that formed an actin cap (supplementary material Fig. S2A,B).…”
Section: The Actin Cap Controls Cell Migrationmentioning
confidence: 98%
“…Although mutations in lamin A or emerin result in non-moving nuclei, TAN lines still glide along the surface of the nuclear envelope (Chang et al, 2013a;Folker et al, 2011). The inner nuclear membrane protein spindle-associated membrane protein 1 (Samp1; also known as NET5 and officially known as TMEM201) is an additional component of TAN lines and functions, in part, to connect Sun2 to lamin A (Borrego-Pinto et al, 2012). On the cytoplasmic side of TAN lines, the formin FHOD1 plays a structural role.…”
Section: Nuclear Migration In Polarizing Adherent Tissue Culture Cellsmentioning
confidence: 99%